(untitled) (The Pakistan Development Review, 1970)
It is now established that the encouraging performance of the agriculture of West Pakistan during the second-plan period took place largely as a result of water-resource development in which private tubewells were particularly important1. According to the pioneering study by the Late Ghulam Mohammad, additional water made available by the tubewells enabled the farmers to: "/) increase the depth of irrigation for existing crops; ii) increase the intensity of cropping by eliminating fallowing and by double cropping; Hi) grow more valuable crops like cotton, rice, fruits and vegetables; iv) increase the use of fertilizer; v) increase the efficiency of bullock use; and vi) increase the output per manual worker" [4, p. 44].